Efficacy of two commercially available dentifrices in reducing dentinal hypersensitivity - Prasad KVV; Sohoni R; Tikare S; Yalamalli M; Rajesh G; Javali S (Wolters Kluwer Medknow Publications, 2010)
Objective: A parallel design clinical study evaluated reduction in hypersensitivity after brushing for 12 weeks with Anchor toothpaste (containing potassium citrate, zinc citrate, triclosan and sodium monofluorophosphate) (test) and Colgate Total (sodium fluoride, silica, triclosan and copolymer) (control) dentifrices. Materials and Methods: Sixty adults with sensitivity to hot and cold stimulus in at least two tooth surfaces were stratified at the baseline examination by tactile, hot and cold stimuli scores in two balanced groups. Subjects were randomly allocated the test and control dentifrices and evaluated after 6 and 12 weeks of dentifrice use for hypersensitivity. Results: The two teeth that were selected in each patient were designated as two different sets. The 12 th -week scores as compared to baseline scores for tactile, heat and cold tests in the test group showed a reduction in tooth hypersensitivity by 36.67% (P < 0.01), 20.35% (P < 0.01) and 53.64 % (P < 0.01), respectively, in the first set of teeth and 43.75% (P < 0.01), 24.48% (P < 0.01) and 59.78% (P < 0.01), respectively, in the second set of teeth. The 12 th -week scores as compared to baseline scores for tactile, heat and cold tests in the control group showed a reduction in tooth hypersensitivity by 42.86% (P < 0.01), 13.02% (P < 0.01) and 45.14% (P < 0.01), respectively, in the first set of teeth and 40% (P < 0.01), 16.59% (P < 0.01) and 44.16% (P < 0.01), respectively, in the second set of teeth. Conclusions: Both the products reduced dentinal hypersensitivity in the study subjects at the end of the 12-week period. However, there was no statistically significant difference in reduction in hypersensitivity between the two products.